A review of air filter test standards for particulate matter of general ventilation. (November 2020) - Yit, Jing Ee; Chew, Bee Teng; Yau, Yat Huang
Air filters play an important role in a heating, ventilation and air-conditioning (HVAC) system to maintain good indoor air quality of a building. The air filter test standards act as a guideline to evaluate the air filter performance. The current global test standard, ISO 16890:2016 adopts particulate matter classification which can be easily understood. The European standard, EN 779:2012 is obsolete and replaced by ISO 16890:2016 in June 2018. ASHRAE 52.2:2017 which adopts the minimum efficiency reporting value (MERV) classification is still widely used in the United States. Some countries in Southeast Asia such as Malaysia, Brunei and Singapore are applying different standards: EN779, ASHRAE 52.2 and ISO 16890. A standardization of the air filter testing and classification is undoubtedly important in the global air filtration market. This paper can act as a reference and assist these developing countries in adopting the suitable air filter testing standard to develop their national standard. As all three standards have no specifications on energy efficiency classification, the energy rating system can be obtained using Eurovent 4/21-2018. The HVAC-system-supplied air quality can be further improved with the consideration of WHO annual mean pollutant limits and EN 16798-3 air classification to determine the supply air cleanliness. Practical application : Although EN 779 is replaced by ISO 16890, some developing countries are still in the transition period. Manufacturers and consumers apply different standards which are EN 779, ASHRAE 52.2 and ISO 16890; therefore, a global filter testing standardization is important. This paper can act as a reference and assist the countries in other regions especially in Southeast Asia to develop respective national standard. Besides, some recommendations are given to improve the air filtration and ventilation system by referring to the WHO guidelines for the air pollutant limits, EN 16798-3 for the supply air quality and Eurovent 4/21 for the air filter energy rating.